Development of E-Handout Based on Local Wisdom of Betawi Traditional Food in Junior High School on Digestive System Materials - Cantika Raisa Handani; Marina Silalahi; Riska Septia Wahyuningtyas (Pro-Life, 2025)
This study aims to examine the nutritional content of traditional Betawi foods and develop an e-handout as a learning medium for the Digestive System material. The research involved 67 students from grades 8A and 8B of SMPN 105 Jakarta and used two methods: Field Exploration to identify food ingredients in traditional dishes, and Research and Development (R&D) in five stages—potential and problems, data collection, product design, validation, and revision—limited by time and cost. Data were collected through product assessment questionnaires and analyzed using percentage scores for each item. The e-handout was validated by six experts: two subject matter experts (V Aiken = 0.81), two media experts (V Aiken = 0.83), and two linguists (V Aiken = 0.92), all categorized as "very feasible." Student responses also showed positive results, with interest at 88.45%, material quality at 87.3%, and language clarity at 89.9%. Overall, the e-handout based on traditional Betawi food was deemed highly feasible and suitable as an accessible learning tool anytime and anywhere.